Effects of load damage on moisture transport and relative humidity response in concrete. (30th April 2018) - Min, Hongguang; Zhang, Weiping; Gu, Xianglin
Highlights: A cylindrical concrete model was presented for relative humidity response. Gained relative humidity response along with moisture transport in damaged concrete. Damage effects were significant on moisture transport & relative humidity response. Drying process of concrete lagged behind wetting process as expected. Hysteresis time based on moisture diffusivity, humidity difference & specimen size. Abstract: In this paper, drying and wetting processes of damaged concrete were studied in-depth along with the relative humidity response. Effects of load damage on relative humidity response and moisture transport were also studied. The results showed that the moisture loss and water absorption all represented a linear relationship with the time square root; besides, the moisture transport accelerated with the increment in load damage. However, during the drying process, moisture transport naturally lagged behind the wetting process as expected. In addition, a hysteresis effect for relative humidity response always exists in damaged concrete. The relative humidity response rate accelerated speedily with the incremental load damage, varying rapidly at first, but then assumed a steadier rate, decreasing with time. This paper also presents a moisture conductivity model for damaged concrete and a relative humidity response model for cylindrical concrete. The results revealed that moisture diffusivity affected the hysteresis time of the relative humidity response. This cannot be neglected when analyzing concrete damage causes and life span. The same holds true for the effects of humidity difference and specimen size. Moreover, the effect of load damage on relative humidity response increased with the incremental specimen size.